Inculating Undergraduetes with Entrepreneurial Characteristics - Aweng Eh Rak; Ahmad Anwar Mohamed Ismail; Wong Yee Ching; Nurul Syazana Abdul Halim; Yah Awg Nik (2010)
The Ministry of Higher Education in Malaysian has published the policy for Entrepreneurial Development in Higher Educational Institutions recently. This agenda was listed in the National Higher Education Strategic Plan as a critical Agenda Project (CAP). The spirit of this agenda is especially to groom students with entrepreneurial criteria to prepare them for the real job tasks. The government hopes that graduates from local universities will be able to create their own business and create jobs for other with their entrepreneurial properties. Local universities have been given a heavy task in inculcating entrepreneurial characteristics among the students. To create entrepreneurial skills need a lot practical exposure. Most of the universities in the country especially public universities adhere to two main approaches. The practical approach can be further divided into two approaches namely academic practical and non-academic practical. Academic practical is stated clearly in the syllabus, while non-academic is done by students when they run business in the campus. Some of the universities have created business environment or entrepreneurial in campus such as Student Mall, Business Incubator, business kiosks and others. We strongly believe that, we have not done enough? Have we practiced the right things? We believed we are doing the right thing but we have not accomplished enough. All the approaches that we have mentioned are actually in the academic framework or academic environment. They are not real scenario, but only simulations. Normally students are unable to sustain what they have learnt in the universities to face the challenge in the real world after they graduated. Consequently if we aim to succeed in inculcating entrepreneurial traits among the students so that they can become independent, a real business exposure should follow after they have completed their academic programme under university’s supervision. The paper illustrates some approaches needed to equip students with knowledge and skills usually employed by businessmen in real business world.